GAMBARAN HASIL PEMERIKSAAN HEPATITIS C PADA PASIEN GAGAL GINJAL KRONIK (GGK) YANG MENJALANI HEMODIALISA DI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA - Ice Ratnalela Siregar; Sri Wahyuni (Poltekkes Kemenkes Medan, 2022)
Chronic Kidney Disease (CKD) is a pathophysiological process with diverse etiologies, resulting in a progressive decrease in kidney function, and generally ending in renal failure. CKD is a clinical condition characterized by an irreversible decrease in kidney function that requires kidney replacement therapy in the form of dialysis or kidney transplantation. According to data from the Indonesian Nephrology Association in 2015, it is estimated that there are 90 thousand people with Chronic Kidney Disease in Indonesia, but those detected to suffer from terminal stage chronic kidneys from those undergoing dialysis (hemodialysis) are only up to five thousand to six thousand. Dialysis is a process of separating macromolecules from ions and low molecular weight compounds in solution by utilizing differences in their diffusion rates through semi-permeable membranes. One of the main techniques used in dialysis is hemodialysis. The basic principle of hemodialysis technique is the diffusion of solutes and water from plasma to dialysis solutions in response to certain differences in concentration and pressure. This technique has a risk of infection because it uses direct access to blood vessels. One of the infections that can occur in hemodialysis is infection from the hepatitis C virus. Immunochromatographic examination method ASSAY (ICA) or called the strip test (Strip Test), which is only by dripping a sample and diluents / buffer into a strip test and in certain incubation the results can already be seen with the eyes without the help of certain tools. (Standart Diagnostics, INC). Based on the sex of patients who are male infected with hepatitis C virus as many as 4 people (20%), while those who are female as many as 3 people (15%), based on the length of time to do hemodialysis, patients who are positive for Hepatitis C virus < 1 year the duration of hemodialysis is 2 people (10%), and those infected with Hepatitis C virus > 1 year as many as 5 people (25%).